Religious affiliation as a driver of immunization coverage: Analyses of zero-dose vaccine prevalence in 66 low- and middle-income countries - Santos, Thiago M.; Cata-Preta, Bianca O.; Wendt, Andrea; Arroyave, Luisa; Hogan, Daniel R.; Mengistu, Tewodaj; Barros, Aluisio J. D.; Victora, Cesar G. (Frontiers in Public Health, 2022)
Background: The literature on the association between religion and immunization coverage is scant, mostly consisting of single-country studies. Analyses in low and middle-income countries (LMICs) to assess whether the proportions of zero-dose children vary according to religion remains necessary to better understand non-socioeconomic immunization barriers and to inform interventions that target zero-dose children. Methods: We included 66 LMICs with standardized national surveys carried out since 2010, with information on religion and vaccination. The proportion of children who failed to receive any doses of a diphtheria-pertussis-tetanus (DPT) containing vaccine – a proxy for no access to routine vaccination or ‘zero-dose’ status – was the outcome. Differences among religious groups were assessed using a test for heterogeneity. Additional analyses were performed controlling for the fixed effect of country, household wealth, maternal education, and urban-rural residence to assess associations between religion and immunization. Findings: In 27 countries there was significant heterogeneity in no-DPT prevalence according to religion. Pooled analyses adjusted for wealth, maternal education, and area of residence showed that Muslim children had 76% higher no-DPT prevalence than Christian children. Children from the majority religion in each country tended to have lower no-DPT prevalence than the rest of the population except in Muslim-majority countries. Interpretation: Analyses of gaps in coverage according to religion are relevant to renewing efforts to reach groups that are being left behind, with an important role in the reduction of zero-dose children.